OFFLINE WEB BROWSING FOR MOBILE DEVICES - KAO, YUNG-WEI; CHOW, TUNG-HING; YUAN, SHYAN-MING (Journal of Web Engineering, 2010)
Based on the advancements of mobile device, mobile platform, and wireless network technology, browsing Web pages on mobile devices have become more popular. However, with its difference from the Web browsing behaviour on desktop, mobile Web browsing suffers from more environmental challenges. Traditionally, Web pages can only be viewed with stable telecom or wireless network connection. In recent years, Google Gears has been proposed to enable the offline Web browsing on mobile devices. However, the Google Gears mechanism can only be used with the server-side library supported by Web Servers. The authors proposed a Web content middleware with personalized interest list to support offline Web browsing on mobile devices, even though the selected Web servers do not support the server-side Google Gears mechanism. Finally, we compare other offline Web browsing solutions with ours and evaluate the offlineable rate of our framework.